2003
DOI: 10.5194/angeo-21-1039-2003
|View full text |Cite
|
Sign up to set email alerts
|

The intermediate layers and associated tidal motions observed by a digisonde in the equatorial anomaly region

Abstract: Abstract. This investigation presents an initial attempt toanalyze a full year of daily ionosonde observations relevant to the determination of plasma densities, tidal structures, and ion transports in the equatorial anomaly region of the lower ionosphere. Particular focus is on the intermediate layers, their seasonal and diurnal variations, and cause-effect relationships. The ionogram database was recorded using a digisonde portable sounder (DPS) at National Central University (NCU, 24 • 58 N, 121 • 11 E) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
4
23
1
Order By: Relevance
“…More recently, using the Arecibo radar observations, Christakis et al [2009] reported the occurrence of intermediate layers twice a day and the daytime descending layers were found to occur in the height range of 130–140 km beginning at ∼1100 LT (for details, see their Figure 3), which are consistent with those reported earlier by Tong et al [1988]. Daytime descending intermediate layers have also been reported from other low latitudes based on ionosonde observations [e.g., Lee et al , 2003; Niranjan et al , 2010]. The above investigations clearly suggest that the occurrence of the intermediate layers is primarily governed by semidiurnal tidal winds.…”
Section: Discussionsupporting
confidence: 87%
“…More recently, using the Arecibo radar observations, Christakis et al [2009] reported the occurrence of intermediate layers twice a day and the daytime descending layers were found to occur in the height range of 130–140 km beginning at ∼1100 LT (for details, see their Figure 3), which are consistent with those reported earlier by Tong et al [1988]. Daytime descending intermediate layers have also been reported from other low latitudes based on ionosonde observations [e.g., Lee et al , 2003; Niranjan et al , 2010]. The above investigations clearly suggest that the occurrence of the intermediate layers is primarily governed by semidiurnal tidal winds.…”
Section: Discussionsupporting
confidence: 87%
“…Using the MIRE model, Resende et al (2017aResende et al ( , 2017b verified that the diurnal component of the zonal wind is very important in the formation of the Es-layers (at 90-140 km) over Brazil; however, the descending movement is simulated only when the meridional wind is included in the model. Lee et al (2003) found for an equatorial anomaly region in Japan that the semidiurnal tide mode is dominant in the spring and winter, while the quarterdiurnal prevails in summer/autumn. For an Indian station, Niranjan et al (2010) observed a high occurrence probability in winter, moderate occurrence rate during equinox and low occurrence during summer solstice.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of some nocturnal IL's over CP and SL during almost all season (except during the June solstice in SL) was another differential factor observed in our study. As mentioned by Lee et al (2003), this result may be influenced by a limitation in the Digisonde, when the plasma frequency is lower than the lowest sounding frequency (1MHz), or by a blanketing caused by an underlying Es layer (l/f type). Over Arecibo, a middle latitude region, for example, the nocturnal IL is a very common phenomenon (Shen et al 1976;Osterman et al 1994).…”
Section: Discussionmentioning
confidence: 98%
“…The Collm meteor radar measures mesospheric and lower thermospheric winds at altitudes of about 80-100 km since summer 2004 (Jacobi et al, 2007(Jacobi et al, , 2009Lilienthal and Jacobi, 2015). These observations have already been used for comparison with SDT, TDT, and QDT components in Es at these heights (Arras et al, 2009;Fytterer et al, 2013;Jacobi et al, 2018a), but for different time intervals, and without providing an overview of all tidal components together.…”
Section: Introductionmentioning
confidence: 99%